SALMONELLA INFECTION AMONGST FOOD WORKERS IN LAHORE - Ullah, Sajjad; Bashir, Saira; Qasim, Akif (Journal of Ayub Medical College Abbottabad, 2017)
This descriptive observational study was conducted at Pathology lab Jinnah hospital, Lahore, January 2013 to October 2015. We include all the food workers in different restaurants, slaughters, inn, recreation centre and bakeries of Lahore for the purpose to identify the salmonella infection, we used Typhoid IgGI/IgM Rapid test device methods (Serum/Plasma), is a lateral flow chromatographic immunoassay technique were calculated. We analysed 1025 individuals, 62 (6%) were found positive for the said diseases out of which 14 (1.3%) IgG positive, 18 (1.8%) IgG IgM positive and 30 (2.9%) were IgM positive. All the individuals who were found positive were without signs and symptoms. Salmonellosis continues to be an important global cause of infectious intestinal disease and spread readily by means of food personnel, zoonotic and contaminated equipments and surface. The screening of the individuals who are silent carriers, help in controlling the spread of salmonella infection in the public. Keywords: Salmonella, typhi; Food Workers; Lahore